Assessing speech at three years of age in the cleft palate population: a scoping review of assessment practices. Issue 2 (20th February 2020) - Fitzpatrick, Beth; Coad, Jane; Sell, Debbie; Rihtman, Tanya
Abstract: Background: There is no consensus in the UK regarding the types of speech samples or parameters of speech that should be assessed at 3 years of age in children with cleft palate ± cleft lip (CP±L), despite cleft units routinely assessing speech at this age. The standardization of assessment practices would facilitate comparisons of outcomes across UK cleft units; earlier identification of speech impairments—which could support more timely treatments; and more reliable recording of therapy impacts and surgical interventions. Aims: To explore assessment practices used to assess speech in 3‐year‐old children with CP±L, including speech parameters, methods of assessment and the nature of the speech sample used. Methods & Procedures: A broad examination of the literature was undertaken through the use of a scoping review conducted in accordance with Joanna Briggs Institute guidelines. Search terms were generated from a preliminary search and then used in the main search (Medline, CINAHL, Embase, AMED and PsycINFO). Main Contribution: A combination of approaches (medical, linguistic, developmental and functional) is required to assess CP±L speech at age 3. A developmental approach is recommended at this age, considering the complexity of speech profiles at age 3, in which typically developing speech processes may occur alongside cleft speech characteristics. A combined measure for both nasal emission and turbulence, and an overall measure for velopharyngeal function for speech, show potential for assessment at this age. Categorical ordinal scales are frequently used; the use of continuous scales has yet to be fully explored at age 3. Although single‐word assessments, including a subset of words developed for cross‐linguistic comparisons, are frequently used, more than one type of speech sample may be needed to assess speech at this age validly. The lack of consensus regarding speech samples highlights a need for further research into the types of speech samples 3‐year‐olds can complete; the impact of incomplete speech samples on outcome measures (particularly relevant at this age when children may be less able to complete a full sample); the impact of different speech samples on the validity of assessments; and the reliability of listener judgements. Conclusions & Implications: Whilst a medical model and linguistic approaches are often central in assessments of age‐3 cleft speech, this review highlights the importance of developmental and functional approaches to assessment. Cross‐linguistic single‐word assessments show potential, and would facilitate the comparison of UK speech outcomes with other countries. Further research should explore the impact of different speech samples and rating scales on assessment validity and listener reliability.